Organizational Red Tapes and their Reflections on Entrepreneurial Orientation: an Exploratory Study of a Sample of Employees in Some Organizations in the Province of Ninewah - خليف سلطان احمد; جميل خالد محمد (Journal of Economics and Administrative Sciences, 2015)
Organizations adopt a number of procedures and instructions in their field of activities in order to aid their resources development and energies to serve their entrepreneurial orientations. This calls for preparing a range of mechanisms to mitigate the strictness and complexity of procedures. The ambiguity and severe complexity of procedures means acknowledging the loss in energy and this in turn impedes the hopes while in the same time weakens the enthusiasm in these organizations and an impedes the possibility to achieve continues innovation, thereby losing opportunities to the level of surrender to the risks and assuming them to be unconquered obstacles. Therefore the researchers sought to frame the problem of their study by asking the following question: are organizational red tapes with their complex form, a confounding factor towards the entrepreneurial orientation process in the investigated organizations? The study adopted a questionnaire form as the main tool to collect data on the phenomenon under study .The researchers utilized a number of statistical tools including (ratios, frequencies. mean, standard deviation, correlation and regression). The main conclusion of the study was expounding a correlation and impact between organizational red tapes and entrepreneurial orientation at the level of the investigated organizations’ sample. The study also provided a number of recommendations